2010
DOI: 10.1007/s10147-010-0123-0
|View full text |Cite
|
Sign up to set email alerts
|

Survival and prognosticators of node-positive cervical cancer patients treated with radical hysterectomy and systematic lymphadenectomy

Abstract: More than two LNM sites and adenocarcinoma were independent prognostic factors for node-positive patients with cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 26 publications
1
28
0
1
Order By: Relevance
“…In addition, the prognostic value of the number of positive LNs was not affected by postoperative RT. In a study by Hosaka et al also found that patients with > 2 positive LNs experienced poorer survival in 108 patients with FIGO IB-IIIB cervical cancer [18]. However, it is unknown whether postoperative CCRT could influence the prognostic value of the number of positive LNs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prognostic value of the number of positive LNs was not affected by postoperative RT. In a study by Hosaka et al also found that patients with > 2 positive LNs experienced poorer survival in 108 patients with FIGO IB-IIIB cervical cancer [18]. However, it is unknown whether postoperative CCRT could influence the prognostic value of the number of positive LNs.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic pelvic lymphadenectomy is an important part of surgical treatment for early-stage cervical cancer. The mean or median number of pelvic nodes removed varied from 13-65 in previous reports (Sakuragi, 2007;Hosaka et al, 2011). In the EORTC-GCG study, removal of more than 11 pelvic nodes was suggested as one of the quality indications for pelvic lymphadenectomy (Verleye et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…3 In the Gynecologic Oncology Group's (GOG) surgical-pathology study of patients with IB cervical cancer, the 3-year disease-free interval was 74% for those with positive nodes versus 86% for node-negative patients. 4 Hosaka et al 5 reported that the survival of patients with cervical cancer with more than 2 lymph node metastasis sites was significantly worse than the survival of patients with 1 or 2 lymph node metastasis sites.…”
mentioning
confidence: 99%